Knowledge, attitude and practice related to sexual health education for people with disabilities among community-based rehabilitation (CBR) workers in Pahang - Zainudin, Nurul Atiqah Sahira; Ismail, Zarina; Windarwati, Heni Dwi; Muda, Siti Mariam; Mustapa Kamal Basha, Muzaitul Akma; Hasan, Haliza (Malaysian Nurses Association, 2022)
Background: Sexual health education is an important component in a person’s well-being. Sexual health is not only focused on sexual relationships, but it also covers on the absence of sexual disease, dysfunction of the sexual organ or infirmity, and respectful, positive ways to approach sexuality. While Community-Based Rehabilitation (CBR) is an accessible centre to manage children with disabilities, to date, there is limited study focusing on understanding related to sexual health education among parents and caregivers of children with disabilities at CBR centre. Purpose: This study aimed to determine the knowledge, attitude, and practice related sexual health education for children with disabilities among CBR workers in Pahang that are involved directly with this vulnerable group. Methods: Cross-sectional survey with convenient sampling method was applied in this study. A total of 100 CBR workers were recruited from various CBR centres throughout Pahang state. A modified questionnaire on knowledge, attitude, and practice on sexual health education was used (Cronbach α=0.638). Results: The findings show that the mean age (SD) of CBR workers was 36.58 ± 8.04. Most of them were Malay (96%) and were female (90%). Mean level of knowledge, attitude, and practice related to sexual health education among CBR workers were 14.10±0.92, 12.13 ± 1.82, and 7.46 ± 1.73, respectively. Most of the socio-demographic characteristics contributed towards knowledge, attitude, and practices related to sexual health education. The R2 values showed that ethnicity (DiffR2 = 4.6%), marital status (DiffR2 = 6.4%), and educational level (DiffR2 = 4.8%) were associated level of knowledge, attitude, and practice on sexual health education. However, there was no significant association found between knowledge, attitude, and practice of sexual health education (p-value> 0.05). Conclusion: In conclusion, the current study shows that CBR workers have good knowledge, positive attitude, and good practice on sexual health education towards people with disabilities. Thus, sexual health education components should be implemented as one of the teaching and learning modules for people with disabilities at CBR centres.